KAWASAKI DISEASE - AN UPDATE - G. Gaedicke; P.J. Hotama; B. Heineking ("Paediatrician" Publishers LLC, 2010)
The lecture presents a modern data on Kawasaki disease - an acute vasculitis with unknown etiology, among children younger than 5 years old. The algorithms of diagnostics and risk stratification are described. Authors review modern recommendation on treatment of children with Kawasaki disease and on peculiarities of their management after convalescence. Key words: children, Kawasaki disease, diagnostics, treatment, complications.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(1):104-115)